Inovação do modelo de negócio: um estudo de caso no IPT - Rubim, Fábio de Rezende (2004)
This paper discusses the innovation of Business Models in organizations. A Business Model is the way a company organizes its resources, abilities and relationships, creating value to its customers. In the current environment of increasing dynamism and competitiveness, companies must develop innovative Business Models in order to differentiate themselves from their competitors, and to create sustainable competitive advantages. Companies like Dell, Amazon, Walmart and Starbucks had developed unique Business Models, which explore their own abilities, and anticipate customer's needs. Many examples of innovative Business Models are described in this paper. The innovation process involves creativity and imagination. Innovative Business Models can be developed through a creativity process of generating ideas and transforming the ideas of best potential into new enterprises. This way companies can create conditions to explore the entrepreneurship potential of its employees. The paper analyses a Case Study in the Institute of Technological Research of São Paulo State (IPT). A new Business Model is suggested to develop the company' entrepreneurship capacity.